Restorasi Keluarga Modern - Saurip Kadi (Musãwa Jurnal Studi Gender dan Islam, 2022)
Potensi diskriminasi pada peran agama memprihatinkan karena sebab-sebab penindasan, malapetaka kemanusiaan pada soalan keluarga dan kaum LGBT (lesbian, gay, bisex dan transgender. Hal ini bertentangan dengan misi dan eksistensi agama. Untuk itu, diperlukan upaya terukur dalam praktek beragama pada esensi ajaran. Hal ini mengembalikan agama sebagai sumber inspirasi bagi kehidupan manusia. Langkah yang perlu ditempuh meliputi   tafsir ulang (hermeneutika) dan perubahan dalam pemahaman makna firman. Tulisan ini bertujuan untuk memberi masukan kepada para tokoh agama dan tokoh sipil sekaligus untuk menawarkan solusi praktis untuk melakukan restorasi keluarga modern yang mengajarkan persamaan hak, penghargaan HAM, serta tegaknya peri keadilan dan peri kemanusiaan bagi setiap orang, tak terkecuali terhadap kaum LGBT. Adapun metoda penelitian yang ditempuh, dengan cara membedah persoalan keluarga dan LGBT, melalui pengkajian sejumlah buku-buku teologi dan hasil penelitian sosial beberapa ahli, di sejumlah negara, disamping dengan melakukan komparasi sejumlah firman dan atau ajaran tentang keluarga dan LGBT dari beberapa agama.  [The potential role of religion becomes a source of discrimination. It is under mis landing an, oppression and humanitarian disasters, including family issues and LGBT (lesbian, gay, bisexual and transgender) activities. This is contrary to the mission and existence of the religions themselves. For this reason, a measured effort is needed so that religious practice returns to the essence of teachings, therefore religions can return as a source of inspiration for human life. Steps that need to be taken include reinterpretation (hermeneutics) or at least a change in understanding the meaning of the verses about family and LGBT in sacred books of religions, redefinition and re-actualization of teachings and the role of religions in society and daily lives. This paper aims to provide input to religious and civic leaders as well as to offer practical solutions on how to restore modern families that teach equality of rights, respect for human rights, and uphold justice and humanity for everyone, including LGBT people. The research method used is by dissecting family and LGBT issues, by examining a number of theological books and the results of social research from several experts, in a number of countries, as well as by comparing a number of words or teachings about family and LGBT from several religions.]